2020
DOI: 10.3390/cells9112456
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Induction of Glycolysis and Oxidative Phosphorylation during Activation of Hepatic Stellate Cells Reveals Novel Mitochondrial Targets to Treat Liver Fibrosis

Abstract: Upon liver injury, hepatic stellate cells (HSCs) transdifferentiate to migratory, proliferative and extracellular matrix-producing myofibroblasts (e.g., activated HSCs; aHSCs) causing liver fibrosis. HSC activation is associated with increased glycolysis and glutaminolysis. Here, we compared the contribution of glycolysis, glutaminolysis and mitochondrial oxidative phosphorylation (OXPHOS) in rat and human HSC activation. Basal levels of glycolysis (extracellular acidification rate ~3-fold higher) and particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Hexokinase and pyruvate kinase activities were carried out using NAD(P)H-linked assays at 37 °C in a Synergy H4 plate reader (BioTek™) at 340 nm for 6 min as previously described [60]. Briefly, for both enzyme measurements, the assay buffer contained 100 mM Tris-HCl, 15 mM NaCl, 0.5 mM CaCl 2 , 140 mM KCl and 5 mM potassium phosphate buffer (pH 7.0).…”
Section: Enzyme Activitiesmentioning
confidence: 99%
“…Hexokinase and pyruvate kinase activities were carried out using NAD(P)H-linked assays at 37 °C in a Synergy H4 plate reader (BioTek™) at 340 nm for 6 min as previously described [60]. Briefly, for both enzyme measurements, the assay buffer contained 100 mM Tris-HCl, 15 mM NaCl, 0.5 mM CaCl 2 , 140 mM KCl and 5 mM potassium phosphate buffer (pH 7.0).…”
Section: Enzyme Activitiesmentioning
confidence: 99%
“…Liver fibrosis (LF) is defined as excessive deposition of extracellular matrix (ECM) in response to various cases of liver injury, which is a reversible abnormal tissue response, and excessive activation of hepatic stellate cells (HSCs) is central to its pathogenesis ( Bataller and Brenner, 2005 ; Zhang et al, 2017 ; Smith-Cortinez et al, 2020 ). LF is the most common pathological consequence of liver diseases and may lead to liver cirrhosis and liver cancer, and even develop into liver failure in severe cases ( Wang Q. et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“… 57 DeWaal et al reported that the upregulation of HK2 begins during liver cirrhosis, increases in dysplasia and reaches peaks in HCC. 56 Furthermore, the upregulation of HK2 and the enhancement of glycolysis have been reported to play pertinent roles in the activation of HSCs and liver fibrosis, 13 , 58 which is the main contributor to liver cirrhosis and HCC. 59 These findings show that targeting HK2 could be an excellent and safe strategy for treating HCC, even in the early phase of hepatocellular carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%